Eothenomys chinensis - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
68. Sichuan Red-backed Vole Eothenomys chinensis French: Campagnol de Chine / German: Sichuan-Rotelmaus / Spanish: Topillo rojo de Sichuan Other common names: Chinese Oriental ole, Pratt's Oriental Vole, Pratt's Vole, Sichuan Chinese Vole Taxonomy. Microtus chinensis Thomas, 1891, “Kia-ting-fu, West Sze-chuen [= Sichuan, Chinal.” Placed into subgenus Anteliomys. Until very recently chinensis included tarquinius and hintoni. Monotypic. Distribution. Mountains along the Dadu River in Sichuan, China. Descriptive notes. Head-body 102-134 mm, tail 57-71 mm; weight 38-57 g. The Sichuan Red-backed Vole is a large species of Eothenomys, with long tail (77-85% of head—body length). Ears are prominent. Females have two pairs of inguinal nipples. Fur is long and soft, dark brown above and slate below. Tail is blackish brown, indistinctly bicolored, and thinly haired. Skull is heavy with prominent crests. Molars are hypsodont and rootless, with thick enamel and not much cement. M? is complex, with five inner salient angles. Habitat. Mountain forests, dense thickets of Rhododendron (Ericaceae), and meadows at elevations of 1500-3400 m. Food and Feeding. No information. Breeding. Reproductive period is from early summer to late autumn. Activity patterns. No information. Movements, Home range and Social organization. No information. Status and Conservation. Classified as Least Concern on The IUCN Red List. Bibliography. Kaneko (1996), Lunde (2008), Luo Jing et al. (2004), Ye Xiaodi et al. (2002), Zeng Tao et al. (2013). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 309, DOI: 10.5281/zenodo.6707142